Legal origins, religion and health outcomes: a cross-country comparison of organ donation laws. Issue 2 (3rd April 2021) - Riambau, Guillem; Lai, Clin; Zhao, Boyu Lu; Liu, Jean
Abstract: This paper investigates what drives countries to legislate presumed consent – making citizens organ donors by default unless they opt out – instead of explicit consent. Results reveal the following: First, civil law predicts presumed consent, which uncovers a mechanism by which an institution that long pre-dates transplantation medicine has an impact on current health outcomes. This is in line with previous research that has found that civil law regimes tend to be more comfortable with a centralized and activist government than common law ones. Second, Catholicism predicts presumed consent. This is consistent with previous research that shows Catholicism generally relies on more hierarchical structures and is less likely to encourage social responsibility among its members. Last, higher pro-social behavior decreases the likelihood of presumed consent. This could be explained by policy-makers trying not to discourage donations where pro-social behavior is high by making it look a requirement rather than an altruistic act. The implications of the findings are discussed, with a particular focus on policy-switches in organ donations.